(untitled) (Italian Journal of Public Health, 2004)
Background. The aim of the study was to determine prevalence of HIV, HCV and HBV among the prisoners of the jails of Southern Latium (Italy). Methods. Design: Cross-sectional study. Participants and Setting: Clinical charts of 2653 prisoners, of whom 940 were of the jail of Cassino, 1581 of the jail of Frosinone and 132 of that of Latina, since 1995 to 1999, were reviewed. Measurement: number of people tested for HIV, HCV and HBV infection and prevalence of diagnosed HIV, HCV and HBV infections. Results. HCV was the most prevalent infection (28.2 %); HBV showed a lower prevalence (26%). Finally, 5.4% of inmates were infected by HIV. Multivariate regression analysis indicated drug addiction, civil status, smoking habit, age (age group 25-34 and 35-44, in respect with people aged 18-24) and Italian nationality as factors mainly associated to HBV, HCV and HIV infection. In particular we found HIV infection associated with the status of drug addiction (OR = 15.8), civil status (OR = 12.6 for widowers; and OR = 2.44 for cohabitants), smoking habits (OR = 3.09) and Italian nationality (OR = 5.39). Similar risk estimates were found for HCV and HBV. Conclusion. High prevalence of blood transmitted infections in jails suggests that diagnostic and preventive measures, as hepatitis B vaccination, but also information and education programs for inmates, are needed to reduce the spreading of such infections, particularly HIV and HCV